EFEKTIFITAS MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA VISUAL TERHADAP HASIL BELAJAR MATEMATIKA KELAS II - Rahma Fahrina Putri; Aryo Andri Nugroho; Siti Kusniati (Jurnal Bionatural, 2024)
This study aims to see the effectiveness of using the Project Based Learning (PBL) model assisted by visual media on grade II mathematics learning outcomes at SDN Karanganyar Gunung 02. This research is a type of quantitative research with a Pre-Experimental Designs research design type OneGroup Pretest-Posttest Design. Data analysis in this study used normality test, one sample t-test, ttest and n-gain test. The normality test is obtained based on pretest values of 0.184 > 0.05. While the results of the postest value showed that 0.398> 0.05. From the normality test result data, it can be concluded that the pretest and postest values have been normally distributed. The one sample t-test concluded that t_hitung = 3,360 > t_tabel = 2,069 or sig. 0.003< 0.05 then Ho is rejected and Ha is accepted. The t-test is obtained based on sig (2-tailed) 0.000 to 0.000 < 0.05, so it can be concluded that there is a significant difference between the results of learning mathematics students before and after the implementation of Project Based Learning (PBL) assisted by visual media on pretest and posttest results. A 2-tailed sig value of 0.000 < 0.05 then H0 is rejected and Ha is accepted. N-Gain Percent obtained 126.0813. Of the existing values between the range of values >76, values located >76 are included in the effective category.